Open-ended coaxial sensor for determination of moisture content, soluble solid content, pH and dielectric properties of Chok Anan mango - Suhaime, Noradira (2018)
The thesis presents the application of open-ended sub-miniature panel (SMA-P) coaxial sensor to determine moisture content, soluble solid content, pH and dielectric properties of Chok Anan mango during ripening from week 5 to week 17 based on reflection coefficient (|S11|) measurement in the frequency range between 1.0 GHz to 4.0 GHz. Measurements were conducted using Keysight FieldFox N9912A Network Analyzer. The mass (M), width (W), length (L), moisture content (m.c.), soluble solid content (SSC) and pH of Chok Anan mango were also measured. All the measured parameters were found to increase non-linearly from week 5 to week 17. This work focus on the internal properties of mango (m.c., pH and SSC) since the external properties (M, W, and L) may not truly represent its internal quality. The SSC and pH methods are only suitable for measurement at later stage of fruit ripeness, i.e. after week 16, which is too late to determine the ripening stage of mango fruits. In contrast, m.c. profiles was distinctively clear to distinguish all the stages of fruit ripeness for the whole 17 weeks of fruit development. Besides that, SSC and pH methods are laborious, difficult, time consuming and destructive whilst the m.c. can be determine fast, accurate and non-destructive using SMA-P coaxial sensor from calibration equations relating to the m.c. to the measured |S11|. The permittivity measurement for the different percentage of m.c. in mango is carried out using the Keysight 85070E dielectric probe kit, later the permittivity values obtained used as an input to calculate the |S11| using Finite Element Method (FEM). FEM was used to determine the accuracy of permittivity measurement by comparing the calculated values of |S11| using FEM with measurement results. Very closed agreements were obtained between measured and calculated |S11| where the mean errors were within 1.5% for all percentage of m.c.. Calibration equations were established to predict the m.c., dielectric constant (ε’) and loss factor (ε’’) from the measured |S11|, where the accuracies for the m.c. and ε’ were highest at 1.0 GHz within 1.5% and 1.6%, respectively, whilst ε’’ was 3.4% at 4.0 GHz. Also, calibration equation has been established to predict pH and SSC values from m.c. obtained from |S11| measurements. The accuracy of pH and SSC were within 3.0% and 5.2%, respectively when compared to standard techniques. The m.c. is the best parameter used to identify the quality of mango since it produced high accuracy based on |S11| measurements using SMA-P coaxial sensor. In conclusion, SMA-P coaxial sensor provides a simple, speedy, non-destructive, flexible and inexpensive approach for the determination of m.c., SSC, pH and permittivity in mango.